Exploration of the Environment, Violence, and Tradition in ”Mata Blater” by Mahwi Air Tawar - Kurniasari Febrianti, Binar; Mahmud, Amir; Ris Riana, Derri; Yulianti, Yeni; Windiyarti, Dara; Syaifuddin; Nurfaidah, Resti; Raudloh, St. (Southeast Asian Language and Literature Studies, 2024)
This study aims to analyze the cultural ecology of the short story anthology "Mata Blater". This collection was selected due to its representation of diverse Madurese customs, traditions, and values, which are infrequently explored by literary authors. The research employs a descriptive exploratory methodology and a cultural ecology approach, utilizing data in the form of literary text units pertaining to cultural ecology. The findings of this investigation demonstrate that this short story collection exhibits a strong correlation with culture and environment, such as karapan sapi, blater, tandak, celurit. Karapan sapi is a traditional bull racing event is not only a showcase of animal prowess but also serves as a celebration of community, culture, and agricultural identity. The preparation for the race involves elements of care for the bulls, emphasizing a relationship steeped in mutual respect and cultural significance. Blater comes from the Madurese language and can be literally translated as "brave" or "champion." However, its meaning and connotations are far more complex within the context of Madurese society. A blater is not merely a thug or a local strongman; they are a highly influential social figure with a dual role as an informal peacekeeper and, at times, a thug for personal gain. The blater represents an informal justice system thriving in a community that holds traditional values dear and reflects the unique social dynamics, beliefs, and power hierarchy within Madurese society. Tandak refers to a female dancer who performs at celebratory events, especially weddings. The role of a tandak is crucial in folk entertainment and has unique characteristics that set her apart from other dancers. A tandak becomes a central figure and a symbol of prosperity at a celebration. A key feature of the Madurese tandak is her interaction with the guests. They dance to the accompaniment of traditional Madurese music, such as saronen, and invite guests to dance with them. Guests who dance with the tandak usually give them a tip (money) as a form of appreciation. Celurit is a traditional sickle used for harvesting illustrates the connection between labor, agricultural practices, and respect for the land. The narratives surrounding celurit highlight the skills passed down through generations and convey the importance of sustainable practices in rice farming. The anthology suggests that these cultural practices embody a collective awareness regarding the interplay of culture, nature, and human well-being. Collectively, these stories emphasize how Madurese people respect, utilize, and preserve their cultural and environmental heritage, underlining the intrinsic value of these interactions for community identity and environmental stewardship. Research has shown that communities around the world employ traditional agricultural practices that enhance biodiversity and ecosystem health, as highlighted in studies on sustainable farming methods. Evidence from environmental psychology suggests that exposure to natural environments can improve mental health and well-being, with studies indicating a positive correlation between time spent in nature and reduced stress levels. Additionally, anthropological research reveals that cultural rituals related to nature conservation can strengthen social ties and promote collective action for environmental protection. These findings underscore the significant role that culture, nature, and the environment play in contributing to human well-being.